Effectiveness of prolonged prone positioning in acute respiratory distress syndrome using mechanical ports: A systematic review - Dewa Ayu Ari Rama Dewi; Tuti Herawati (Holistik Jurnal Kesehatan, 2024)
Background: Acute respiratory distress syndrome (ARDS) is a pulmonary condition that triggers a systemic inflammatory response with different etiologies that has distinctive pathological clinical characteristics. This study discusses the provision of prolonged prone position as supportive therapy to improve oxygenation status in ARDS patients as well as the complications that may arise from prolonged prone position. Purpose: To compile and collect the latest evidence on prolonged prone positioning therapy in ARDS patients. Method: Design a systematic review with PRISMA guidelines using databases from ScienceDirect, Proquest, PubMed, and Scopus. Search for articles with the keywords “prolonged prone position” AND “ARDS” AND “benefits” AND “complications”. Results: All nine articles recognized the positive influence of prolonged prone position on oxygenation status in ARDS patients, but had no effect on patient mortality rates. However, prolonged prone positioning has several complications related to nerve disorders in parts of the body that are under pressure for a long time, prolonged use of sedation medication which affects the prolonged use of mechanical ventilation, long ICU stay, and other complications. In terms of efficiency, prolonged prone positioning provides convenience for health workers because it does not require more time and energy in changing the patient's position repeatedly. Conclusion: Prolonged prone positioning has been proven to be effective and safe for patients. This position can be used and reduces the workload of health care workers, but complications related to this position require good monitoring regarding clinical and neurological parameters. Suggestion: Further research needs to be done regarding the appropriate duration of proneness so that it can provide an optimal positive impact and possibly minimize the risk of complications. Further research involving patient groups may provide a deeper understanding of the benefits and risks of prolonged prone positioning interventions.   Keywords: Acute Respiratory Distress Syndrome (ARDS); Benefit; Complication; Prolonged Prone Position.   Pendahuluan: Acute respiratory distress syndrome (ARDS) merupakan kondisi paru yang memicu respon inflamasi sistemik dengan etiologi yang berbeda yang memiliki ciri-ciri klinis patologis khas. Penelitian ini menganalisis tentang pemberian posisi prolonged prone position sebagai terapi suportif untuk meningkatkan status oksigenasi pada pasien ARDS serta komplikasi yang mungkin ditimbulkan dari pemberian prolonged prone position tersebut. Tujuan: Untuk menyusun dan mengevaluasi bukti-bukti terkini tentang terapi prolonged prone position pada pasien ARDS. Metode: Systematic review design dengan panduan PRISMA menggunakan database dari ScienceDirect, Proquest, PubMed, dan Scopus. Pencarian artikel dengan kata kunci “prolonged prone position” AND “ARDS” AND “benefit” AND “complication”. Hasil: Kesembilan artikel mengakui pengaruh positif prolonged prone position terhadap status oksigenisasi pada pasien dengan ARDS, namun tidak berpengaruh pada tingkat mortalitas pasien. Namun pemberian prolonged prone position memiliki beberapa komplikasi terkait dengan gangguan neurologis pada bagian tubuh yang mendapat penekanan dalam waktu yang lama, penggunaan obat sedasi yang lama yang berpengaruh pada penggunaan ventilasi mekanik yang lama, lama perawatan ICU, dan komplikasinya. Dari segi efisiensi, prolonged prone position memberikan kemudahan bagi tenaga kesehatan karena tidak memerlukan waktu dan tenaga lebih dalam perubahan posisi pasien yang berulang-ulang. Simpulan: Pemberian prolonged prone position (PPP) telah terbukti efektif dan aman untuk pasien. Posisi ini dapat dilakukan untuk mengurangi beban kerja petugas layanan kesehatan, namun komplikasi terkait pemberian posisi ini perlu dilakukan pemantauan yang baik terkait parameter klinis dan neurologisnya. Saran: Perlu dilakukan penelitian lebih lanjut terkait durasi prone yang tepat, sehingga dapat memberikan dampak positif secara optimal dan kemungkinan risiko komplikasi yang minimal. Penelitian lanjutan yang melibatkan kelompok pasien dapat memberikan pemahaman yang lebih mendalam terkait manfaat dan risiko dari intervensi prolonged prone position.